Semitransparent ceramics for heat-insulating covers of the combustion chamber - V. G. Merzlikin; O. V. Sidorov; V. V. Bezdelkin; M. Gutierrez Ojeda (ՀՀ ԳԱԱ հրատ.)
Theoretical study of the semitransparent heat-insulating coatings used for the combustion chamber (CC) of reciprocating engines is made. These coatings will provide the thermal regime at generation in combustion chamber until 50% radiant component heat flow. Model of the samples of porous ceramic materials, were offered as heat-insulating coatings. They are based on powders of zirconium, silicon, aluminum oxide which have transparent bands over the range of radiation wavelengths of the inflamed gas mixture in the combustion chamber of high-speed diesel engines. The radiant - conductive theory of subsurface heat of semitransparent coatings combustion chamber walls under the action of intensive radiant and convection heat flow is discussed. Results of simulation have shown that there is a subsurface temperature maximum inside ceramics under intensive visual and short-range infrared radiation.
Keywords: Քիմիա